PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN TEKNIK PENGOLAHAN PRODUK AGRIBISNIS PANGAN DI DESA BONTULA KECAMATAN ASPARAGA KABUPATEN GORONTALO - Hippy, Mohammad Zubair; Gobel, Muhammad Rizq; Machieu, Siti Rahmatia (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2025)
Community empowerment through training in food agribusiness product processing techniques is a crucial strategy for increasing the added value of agricultural commodities while promoting economic self-sufficiency in rural areas. This activity was conducted in Bontula Village, Asparaga Subdistrict, Gorontalo Regency, with the aim of improving the knowledge, skills, and attitudes of the community in processing corn is the village's dominant crop into value-added products such as corn chips. The methods used in this program included theoretical sessions on food agribusiness, hands-on processing training, and competency evaluations through pre-tests and post-tests. The results showed an increase in the average community competency score from 54.80% (categorized as fair) to 76.60% (categorized as good). Knowledge increased from 60.83% to 81.33%, skills from 51.56% to 64.89%, and attitudes and commitment to adopting information from 50.00% to 82.00%. The paired sample t-test indicated a statistically significant result (p 0.05), confirming a notable difference before and after the training. This program demonstrates the effectiveness of locally based food processing training in enhancing community capacity and supporting agribusiness development in rural areas.Keywords: Empowerment; Food Agribusiness; Corn; Training; Bontula Village